(untitled) - Hart, Brian (Cambridge, UK, 2007)
English in Mind is a four - level course for teenager which combines engaging content with a strong focus on grammar and vocabulary. It takes students from beginner to intermediate level and is ideal for mixed - ability classes.
Keywords: English language,English language,Anh ngữ,Anh ngữ; Study and teaching,Học và Dạy